Cognitive function during exacerbations of chronic obstructive pulmonary disease. Issue 10 (10th October 2019) - Poot, Betty; Travers, Justin; Weatherall, Mark; McGinty, Melinda
Abstract: Background: The reported prevalence of cognitive impairment in patients with stable chronic obstructive pulmonary disease (COPD) ranges 36‐77%. Few studies report the prevalence of cognitive impairment in acutely unwell COPD patients. Aims: To determine the prevalence and time course of cognitive impairment in patients with COPD during and after an admission to hospital with an exacerbation of the disease. Methods: Patients admitted to hospital with an exacerbation of COPD between October 2013 and November 2014 were administered the Montreal Cognitive Assessment tool, COPD assessment test and modified Borg dyspnoea scale at three points in time: within 24 h of admission, between 48 and 72 h after admission and 6 weeks post discharge. Results: Twenty‐five patients agreed to participate. Four withdrew from the study after the initial evaluation. The mean (range) COPD assessment test score 24 h after admission was 26 (18–37). Cognitive impairment was found in 19/25 (76%) patients at the initial evaluation, 16/21 (76%) patients at the second evaluation. Overall, 22/25 (88%) showed cognitive impairment within 72 h of an exacerbation of COPD. Fourteen out of 21 (66%) patients showed cognitive impairment at the final evaluation. The mean Montreal Cognitive Assessment scores improved from admission (22.6) to the second evaluation (23.3) to the final evaluation 3 (24.4), but this change was not statistically significant. Conclusion: Cognitive impairment is highly prevalent during hospital admissions with an exacerbation of COPD. This impairment does improve with time, but only a minority recover within a normal range. This will affect patients' abilities to understand and remember information given to them in hospital and adhere to medication regimens.